Bioactive Polyphenolic Compounds Showing Strong Antiviral Activities against Severe Acute Respiratory Syndrome Coronavirus 2 - Kandeil, Ahmed; Mostafa, Ahmed; Kutkat, Omnia; Moatasim, Yassmin; Al-Karmalawy, Ahmed A.; Rashad, Adel A.; Kayed, Ahmed E.; Kayed, Azza E.; El-Shesheny, Rabeh; Kayali, Ghazi; Ali, Mohamed A. (Pathogens (Basel), 2021)
Until now, there has been no direct evidence of the effectiveness of repurposed FDA-approved drugs against Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infections. Although curcumin, hesperidin, and quercetin have broad spectra of pharmacological properties, their antiviral activities against SARS-CoV-2 remain unclear. Our study aimed to assess the in vitro antiviral activities of curcumin, hesperidin, and quercetin against SARS-CoV-2 compared to hydroxychloroquine and determine their mode of action. In Vero E6 cells, these compounds significantly inhibited virus replication, mainly as virucidal agents primarily indicating their potential activity at the early stage of viral infection. To investigate the mechanism of action of the tested compounds, molecular docking studies were carried out against both SARS-CoV-2 spike (S) and main protease (Mpro) receptors. Collectively, the obtained in silico and in vitro findings suggest that the compounds could be promising SARS-CoV-2 Mpro inhibitors. We recommend further preclinical and clinical studies on the studied compounds to find a potential therapeutic targeting COVID-19 in the near future.